2010
DOI: 10.14742/ajet.1093
|View full text |Cite
|
Sign up to set email alerts
|

"But they won't come to lectures ..." The impact of audio recorded lectures on student experience and attendance

Abstract: The move to increasingly flexible platforms for student learning and experience through provision of online lecture recordings is often interpreted by educators as students viewing attendance at lectures as optional. The trend toward the use of this technology is often met with resistance from some academic staff who argue that student attendance will decline. This study aimed to explore students' use of online lectures and to measure the impact of them on student attendance at lectures. A pre and post evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 14 publications
8
71
3
2
Order By: Relevance
“…In our study, counts of students revealed that attendance frequently fell below 50% of the enrolled cohort, which concurs with the majority of students indicating that they regularly miss at least one lecture a week. It is interesting to note that in some studies [29] low attendance was at 75%, while in others [18], as in this study, attendance fell to much lower levels.…”
Section: Discussionsupporting
confidence: 54%
“…In our study, counts of students revealed that attendance frequently fell below 50% of the enrolled cohort, which concurs with the majority of students indicating that they regularly miss at least one lecture a week. It is interesting to note that in some studies [29] low attendance was at 75%, while in others [18], as in this study, attendance fell to much lower levels.…”
Section: Discussionsupporting
confidence: 54%
“…Yet, empirical evidence for this fear is ambiguous (O'Callaghan et al 2015). While some studies found no decreases in lecture attendance (Larkin 2010;Moss et al 2010;Walls et al 2010), others found that students skipped lectures, especially if podcasts were provided as a supplementary review resource (Brotherton and Abowd 2004;Traphagan et al 2010). The low attendance rates in the present survey suggest a decrease in lecture attendance when podcasts are introduced.…”
Section: Focus On Podcasts Neglect Of Face-to-face Lecturesmentioning
confidence: 62%
“…In contrast, when a professional presenter gave the podcast, students did not like the voice or tone because it sounded unnatural, and they did not trust the unknown voice. There is still great interest in recording lectures, as recent research suggests (e.g., Larkin, 2010;McGarr, 2009;Scutter, Stupans, Sawyer & King, 2010).…”
Section: Voicementioning
confidence: 99%